"The Electronic Preceptor"—Use of Email to Provide Feedback to Students on Their Suturing Compared to Direct Observation and Direct Feedback in Third-Year Medical Students During Their OB/GYN Clerkship. (October 2017) - Sutton, Jill M.; Guyton, Lisa M.; Hodson, Charles; Nelson, Keith H.; Learman, Lee A.
Abstract : OBJECTIVE: To assess medical students' preferred method and timing of feedback on suturing skills. METHODS: This study was a quasi-experimental study involving 3rd-year medical students on the OB/GYN Clerkship at East Carolina University (IRB approved exempt). Students were preassigned by the clerkship director based on prior subrotation experience to digital feedback (n=32) or direct feedback (n=35) for each cohort. Upon arrival to the clerkship, students receive instruments, suture, and access to the "Duke Suture Skills Course" video. During Simulation Day (Week 3), students received either "Direct Feedback" immediately by a resident colleague or "Digital/Indirect Feedback" from the Clerkship Director via email shortly after the session. Suturing was performed on contraceptive implant model arms. Feedback preferences were assessed using a questionnaire asking students their level of agreement with six statements regarding the effectiveness of the feedback they received (5-point Likert scale ranging from 1=strongly disagree to 5=strongly agree). Mean responses were compared using the Mann Whitney U Test and a statistical significance threshold of P <.05. RESULTS: Direct feedback by a resident colleague was superior to indirect/digital feedback by an expert in perceived skill acquisition (4.53 versus 3.60, P <.001), skill correction (4.50 versus 3.71, P <.001) and value to the learner (4.63 versus 4.29, P <.01). Small mean differences in skill confidence, perceived suturing independence, and the quality of the learning environment were not statistically significant. CONCLUSION: Immediate feedback may be valued more by medical students learning suturing skills than indirect feedback, but may not promote more skill confidence or independence.